2016
DOI: 10.1016/j.aott.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Is surgeons' experience important on intra- and inter-observer reliability of classifications used for adult femoral neck fracture?

Abstract: PurposeTo evaluate whether surgeons' experience affect inter- and intra-observer reliability among mostly used classification systems for femoral neck fractures.Material and methodsA power point presentation was prepared with 107 slides which were antero-posterior radiographs of each femoral neck fracture. Five residents, 5 orthopaedic surgeons and 5 senior orthopaedic surgeons reviewed this presentation and classified the fractures according to Garden, Pauwels and AO classifications. The order of the slides w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The overall kappa value was 0.31 (0.38 for the surgeons and 0.27 for the residents). Turgut et al [45] reported on the inter-and intraobserver reliability of the Garden, Pauwels, and AO classification systems and whether surgeon experience influenced results. In their study, 15 observers were asked to review preoperative AP radiographs of 107 patients with femoral neck fractures on two separate occasions.…”
Section: Validitymentioning
confidence: 99%
“…The overall kappa value was 0.31 (0.38 for the surgeons and 0.27 for the residents). Turgut et al [45] reported on the inter-and intraobserver reliability of the Garden, Pauwels, and AO classification systems and whether surgeon experience influenced results. In their study, 15 observers were asked to review preoperative AP radiographs of 107 patients with femoral neck fractures on two separate occasions.…”
Section: Validitymentioning
confidence: 99%
“…Our data supports this, as we could show the best inter-rater reliability in the two-staged classification in femoral neck fractures. Although all three observers are experienced consultants for traumatology and have a high intra-rater reliability, they were not able to perform more than a moderate inter-rater reliability in the Garden and AO classification, but this is according to the literature ( 11 ).…”
Section: Discussionmentioning
confidence: 98%
“…Each fracture is seen in our emergency department by an experienced trauma surgeon before admission to the ward, which limits the generalization to other hospitals or healthcare systems if only emergency registrars see the patient before operation. However, as mentioned above, experience seems to be of little influence for classification of these fracture types ( 11 ). Furthermore, as this is a retrospective study, the results should be verified by a prospective study.…”
Section: Discussionmentioning
confidence: 99%
“…In the past the Pauwels classification has also been studied, resulting in a poorly reliability classification and therefore no longer used in daily clinical practice [ 20 ] [ 21 ].…”
Section: Discussionmentioning
confidence: 99%